Auricular acupressure for constipation in adults: a systematic review and meta-analysis - Jiang, Ze-Fei; Liu, Guang; Sun, Xiao-Xiang; Zhi, Na; Li, Xue-Mei; Sun, Ran; Zhang, Hong (Frontiers in Physiology, 2023)
Introduction: Auricular acupressure (AA) has been widely utilized in the management of constipation, with several studies suggesting its efficacy in treating constipation patients. However, the safety and effectiveness of AA in constipation remain uncertain. Hence, the aim of this study was to assess the effectiveness and safety of AA for constipation. Methods and analysis: A total of eight electronic databases and three clinical trial registration platforms were searched from their inception to April 2023 for randomized controlled trials (RCTs) of AA for constipation. The included studies were appraised for quality using the Cochrane Collaboration's Risk of Bias Assessment tool. The quality of evidence was assessed by two independent reviewers employing the Grading of Recommendations Assessment, Development, and Evaluation System (GRADE) evaluation tool. Meta-analysis of data and assessment of publication bias were performed using RevMan 5.4 and STATA 13.0 software, respectively. Results: This review included 34 randomized controlled trials conducted between 2007 and 2023, involving 2465 participants. The findings of the study indicate that overall, AA is significantly associated with improved CSBMs (MD = 1.22, 95% CI [0.68, 1.77], P<0.0001, I 2 = 0%), BSF (MD = 0.72, 95%CI: [0.15,1.28], P=0.01, I 2 = 82%), CAS (MD =-3.28, 95%CI: [-5.95, -0.60], P=0.02, I 2 =80%), responder rate (RR = 1.27, 95%CI: [1.16, 1.38], P<0.00001, I 2 = 79%), cure rate (RR = 1.84, 95% CI [1.56, 2.15], P < 0.00001, I 2 = 0%), and PAC-QOL (MD = -2.73, 95 % CI: [-3.41, -2.04], P<0.00001, I 2 = 98 %) compared to the control group. However, no difference in PAC-SYM (MD = -0.15, 95%CI: [-0.38,0.07], P=0.19, I 2 = 67%) was found between the two groups. Additionally, there was no significant difference in adverse events (RR =0.53, 95 % CI: [0.24, 1.21], P=0.13, I 2 = 38 %).Based on the available evidence, auricular acupressure appears to be a potentially safe and effective intervention for managing constipation in adults. Nonetheless, the overall quality of evidence for the identified outcomes was assessed as low to very low, highlighting the need for additional high-quality randomized controlled trials to further validate these findings.